2015
DOI: 10.1071/ch14328
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Bioevaluation of Novel Oxa-Caged Garcinia Xanthones as Anti-Tumour Agents

Abstract: Gambogic acid (GA), a special category of Garcinia xanthones, has attracted great attention owing to its striking bioactivities and unique structure. To further explore its structure-activity relationship, we prepared seven novel oxa-caged Garcinia xanthones that were for the first time varied at the C-2 position of B ring and at the C-21/22 or C-23 position of the prenyl group in the caged scaffold. Some compounds exhibited strong anti-proliferation activities in different cancer cell lines. Particularly, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Modifications of the C-27/28 double bond to a dihydroxyl or epoxy group enhance cytotoxicity against the A549, MCF-7 and BGC-823 cell lines, among which the epoxy group confers better inhibition than the dihydroxyl group, except against A549 cells [162]. Functionalization of the carboxylic acid moiety at C-29 appears to be tolerated, thus indicating that this group could be modulated to improve physiochemical properties [99,109,159].…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modifications of the C-27/28 double bond to a dihydroxyl or epoxy group enhance cytotoxicity against the A549, MCF-7 and BGC-823 cell lines, among which the epoxy group confers better inhibition than the dihydroxyl group, except against A549 cells [162]. Functionalization of the carboxylic acid moiety at C-29 appears to be tolerated, thus indicating that this group could be modulated to improve physiochemical properties [99,109,159].…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…Functionalization of the carboxylic acid moiety at C-29 appears to be tolerated, thus indicating that this group could be modulated to improve physiochemical properties [99,109,159]. Introduction of an electron withdrawing group at C-29 improves the inhibitory activity against A549 cells [162]. Moreover, introduction of a hydrophilic amine side chain at C-31 maintains cytotoxicity while increasing water solubility and cell permeability, whereas a hydrophobic amine moiety diminishes the bioactivity [104].…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Miao et al [ 117 ] developed small molecule entities inspired by the structure of gambogic acid. They focused on modifications of the prenyl moiety of the caged xanthones which led to synthesize seven derivatives 149 – 155 ( Figure 14 ), which were tested for anti-tumor activity [ 117 ].…”
Section: Synthetic Chiral Derivatives Of Xanthonesmentioning
confidence: 99%
“…Although these experiments were preliminary, the results suggested that promising agents with anti-tumor activities could be obtained by modification at C-2 position of the B ring and at C-21/22 or C-23 position of the prenyl group in the caged scaffold. The formation of dihydroxy and epoxy groups of the double bond at C-21/22 and the introduction of an electron-withdrawing group at C-23 evidently affected the anti-proliferation activity [ 117 ]. In Table 1 a summary of the synthetic CDXs inspired in natural xanthones and their described biological activities are presented, as well as the associated references.…”
Section: Synthetic Chiral Derivatives Of Xanthonesmentioning
confidence: 99%